Observations on decadal sandbar behaviour along a large‐scale curved shoreline. Issue 2 (17th January 2021) - Gijsman, R.; Ruessink, B.G.; Visscher, J.; Schlurmann, T.
Abstract: Nearshore sandbars are characteristic features of sandy surf zones and have been observed with a variety of geometries in cross‐shore (e.g. location) and longshore direction (e.g. planform). Although the behaviour of sandbars has been studied extensively on spatial scales up to kilometres and timescales up to years, it remains challenging to observe and explain their behaviour on larger spatial and temporal scales, especially in locations where coastline curvature can be prominent. In this paper, we study a data set with 38 years of coastal profiles, collected with alongshore intervals of 50 m, along the 34 km‐long curved sandy shoreline of Sylt island, Germany. Sylt's shoreline has an orientation difference of 20° between the northern and southern half of the island. We found that the decadal coastal profiles on the southern half show features of a low‐tide terrace and a sandbar located further from the shoreline ( 441 m). On the nothern half, the sandbar was located closer to the shoreline ( 267 m) and was less pronounced, while the profiles show transverse bar and rip features. The alongshore planform also differed systematically and significantly along the two island sides. The sandbar on the southern island half, with alongshore periodicity on a larger length scale ( 2240 m), was coupled out‐of‐phase to the shoreline, while no phase coupling was observed for the sandbar with periodicity on a shorter length scale ( 670 m) on the northern half. We related the observed geometric differences of the sandbars to the difference in the local wave climate along Sylt, imposed by the shoreline shape. Our observations imply that small alongshore variations in wave climate, due to the increasing shoreline curvature on larger spatial scales, can lead to significant alongshore differences in the decadal evolution of coastal profiles, sandbars and shorelines. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Alongshore differences in wave climates, imposed by shoreline curvature, can lead to significant alongshore differences in the decadal evolution of shorelines and sandbars.